2013
DOI: 10.1371/journal.pone.0059927
|View full text |Cite
|
Sign up to set email alerts
|

Pyrosequencing Reveals High-Temperature Cellulolytic Microbial Consortia in Great Boiling Spring after In Situ Lignocellulose Enrichment

Abstract: To characterize high-temperature cellulolytic microbial communities, two lignocellulosic substrates, ammonia fiber-explosion-treated corn stover and aspen shavings, were incubated at average temperatures of 77 and 85°C in the sediment and water column of Great Boiling Spring, Nevada. Comparison of 109,941 quality-filtered 16S rRNA gene pyrosequences (pyrotags) from eight enrichments to 37,057 quality-filtered pyrotags from corresponding natural samples revealed distinct enriched communities dominated by phylot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
52
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(58 citation statements)
references
References 59 publications
(58 reference statements)
5
52
1
Order By: Relevance
“…Three cellulolytic in situ enrichment cultures from the GBS site include 42000 Thermotogae-like contigs with X90% similarity to the genomes used in this study (Supplementary Table S7), consistent with 16S rRNA analysis (Peacock et al, 2013). Comparisons of Thermotogae-like sequences among the three cultures revealed that they are 498% identical across homologous contigs 45 kb in length, again demonstrating low within-site diversity for TM-group bacteria.…”
Section: Resultssupporting
confidence: 74%
“…Three cellulolytic in situ enrichment cultures from the GBS site include 42000 Thermotogae-like contigs with X90% similarity to the genomes used in this study (Supplementary Table S7), consistent with 16S rRNA analysis (Peacock et al, 2013). Comparisons of Thermotogae-like sequences among the three cultures revealed that they are 498% identical across homologous contigs 45 kb in length, again demonstrating low within-site diversity for TM-group bacteria.…”
Section: Resultssupporting
confidence: 74%
“…After incubation, the bags were removed, homogenized, and distributed into a sterile 50 mL polypropylene tube as described above for sediments. Details of lignocellulose degradation and 16S rRNA gene pyrosequencing were reported previously (Peacock et al, 2013). …”
Section: Methodsmentioning
confidence: 99%
“…The sample code for cellulolytic enrichments consists of three parameters, temperature (77°C or 85°C), cellulose substrate (A, aspen shavings; C, corn stover), and incubation environment (W, suspended in water; S, buried in sediment) as described earlier (Peacock et al, 2013). As described in Peacock et al (2013), the temperature at each incubation site (within 0.5 meters of each lignocellulose enrichment) was tracked for the majority of the duration of the incubation using high-temperature iButtons (Maxim Integrated, San Jose, CA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A specific example is the degradation of glucurono-xylan [18], the major hemicellulose of Arundo donax (giant reed) a fast growing and low input-high yielding energy crop [19] The enzymatic degradation of this linear polymer of ␤-1,4-linked d-xylopyranosyl units frequently substituted with ␣-1,2 linked glucuronate residues, which are often methylated on the C4 (MeGlcA) [20] occurs by the concerted action of xylanases and ␣-glucuronidases; thus, we embarked in the search for novel enzymes of this kind in the genomes of (hyper) thermophilic microorganisms which are known for containing unique (hemi) cellulolytic systems [21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%